BARC model solar dryer compared with a modified dryer for drying fish products - Lipilata khuntia (kufos, 2014)
Abstract- Drying efficiencies of the BARC model solar drier, modified BARC solar drier and conventional solar drying in the preparation of dried fish products was studied. Quality of six dried products prepared employing the different methods was assessed. Drying patterns of different dried products prepared using the BARC model and modified version were compared with products prepared by conventional drying on a wooden platform, which served as the control. Temperature in BARC drier was as high as 60-65 ̊ C, in modified type drier it could be controlled below 55 ̊ C, which is suitable for drying most fish products, without overheating. Six types of products were prepared – dried raw fish fillet, dry salted fish fillet, dried raw prawn meat, dried cooked prawn meat, fish meal and fish prawn concentrate. Mackerel was used for preparing fillets, flower tail prawn for prawn meat, anchovy for fish meal and pink perch for FPC. Drying time for all the products studied were the lowest in the modified BARC drier, and the highest in conventional drying. The extent of all spoilage quality indices were substantially lower and sensory quality higher in the products dried by BARC model drier and modified BARC drier as compared to conventional drying. Between the two driers, the modified drier resulted in better quality products. Storage studies of two months duration were also carried out on the products prepared. Products dried by modified BARC drier were in general superior, followed by those dried in BARC model drier, those dried in the open were of comparatively lower quality.